Respuesta del cultivo de alstroemerias (alstroemeria aurantiaca) a la aplicación de tres dosis de ácidos húmicos y ácidos fúlvicos, en el mejoramiento de la producción, en la zona de Cayambe, provincia de Pichincha - Túqueres Alvarez, Milton Medardo (2013)
Due to the deteriorated conditions of the soil, the Alstroemerias production in Ecuador is affected in both quality and quantity. There is a little production of Alstroemerias’ stems for export. The main problem is the lack of quality of harvested stems that must meet certain parameters to be exported (length, weight, caliber, color, flower size) and the limited availability of new techniques and alternative crop production of Alstroemeria. This research was developed in the province of Pichincha, town of Cayambe, Orongoloma community, located at 3000 masl, in order to determine the effects of humic and fulvic acids in different doses in Alstroemerias cultivation in greenhouses to improve their performance. A design randomized complete block was used with a factorial arrangement (A x B) + 1 where the factor A are the acids (humic and fulvic) and B (dose) factor.